An evaluation of genetic editing in terms of its impact on free will, genetic determinism and reason-responsiveness - Lendrum, Tristan (University of the Witwatersrand, Johannesburg, 2024)
Genetic editing has advanced at an ever-increasing speed over the past five decades and has sparked curiosity from all corners of academia. This paper discusses genetic editing in terms of its interaction with philosophical topics relating to the freedom of will. A vast collection of literature has already been published regarding the ethical considerations of genetic editing, however, in this paper I put those concerns to the side and seriously analyse the impact a complete practice of genetic engineering would have on our free will in the context of a moderately reasons responsive framework. Theoretically, the discussion occurs under the theoretical position of compatibilism. The main claim of the argument which develops in this paper is that genetic editing is uniquely positioned to expand our scope of free will in line with a moderately reasons responsive understanding of free will.
A research report submitted in fulfillment of the requirements for the Masters in Philosophy, In the Faculty of Humanities, School of Social Science, University of the Witwatersrand, Johannesburg, 2024
Keywords: UCTD; Gene Editing; Gene by environment Interaction; Genetic Engineering; Compatibalism; Free Will; Reasons Responsiveness; SMA; SDG-4: Quality education